Main factors behind price fluctuations in food market and its impacts on purchasing power of people in Azerbaijan - Allahverdiyev, Seymur (My University, 2023)
Increasing food prices, high rates of inflation have significantly affected the purchasing power of consumers over the years. Price fluctuations led to the higher food insecurity, limited access to the important nutrition items and resulted in aggravation of poverty. The current scale of global crisis on hunger and undernutrition is tremendously increasing. Due to WFP (2023), it is estimated that 345 million people in 79 countries are currently facing the harsh levels of food insecurity in the year of 2023. These statistics have doubled since 2020 from the period of COVID-19. This represents a surprising increase of 200 million people in comparison to before pandemic levels. It seems that ongoing price fluctuations in the food market is going to continue as the global conflicts are aggravating and world population is increasing. Market prices for agricultural goods has significantly increased a year after Russia invaded Ukraine. Though there is a slight decrease in prices in comparison to early 2022, but still extension of the war between world’s largest exporters of wheat and other essential crops to the second year puts many countries to face the excessive food insecurity. According to IMF (2023) Fragile and conflict-affected states, home to 1 billion people, are at particular risk. During the last years Azerbaijan has particularly developed in terms of economic growth and diversification. However, geopolitical impacts of war between Russia and Ukraine have also affected to the food security of Azerbaijan. Country strongly relies on imports for its certain food items as: meat and dairy products. Any kind of disruptions in international trade may lead to the higher prices for indispensable nutrition products, less purchasing power of consumers to acquire these food items and more importantly it may result for the shortages which causes danger for food security. When studying the conditions that were present leading up to the 2007–2008 global food crisis and the 2010–2011 food price inflation that contributed to the Arab Spring, we observe even higher risks to the global food system today (McKinsey, 2022). Significant and unexpected spikes in food prices pose challenges for low-income families to adapt, leading to a decline in consumer spending, decreased access to sufficient calories and nutrition which push people into poverty and hunger. When the prices for food products in domestic market remarkably increases, buyers are experiencing a decline in their ability to acquire certain goods. Especially low-income families allocate a significant portion of their income towards food (50-70 percent), because they face a greater challenge in adapting to increased food prices rather than other income groups. While investigating the recent studies on this topic it became obvious that, there is a lack of data and evidence about the outcomes of food price fluctuations on people. Therefore, this capstone project seeks to find out the factors causing for food price fluctuations in Azerbaijan market and provide appropriate policy recommendations for decreasing its outcomes on people.
Keywords: Food prices -- Economic aspects -- Azerbaijan.; Inflation -- Effects on food prices -- Azerbaijan.; Poverty -- Impact of food price fluctuations -- Azerbaijan; Agricultural prices -- Global influences -- Azerbaijan.; Food price inflation -- Effects on low-income families -- Azerbaijan; Public policy -- Food security -- Recommendations for Azerbaijan; Public and International Affairs